(untitled) (TAMADDUN NURI JURNALI, 2024)
In the article, the changes that occurred in the system of pedagogical education and pedagogical staff training in the Uzbek SSR in the years after the Second World War, the reforms implemented by the Soviet authorities in the field of higher education and secondary special education, laws and decisions, problems in their implementation, achievements in the field of pedagogical education efforts were made to highlight the achievements and problems in the education system based on available sources.